Pengaruh Warna, Tipografi, dan Layout pada Desain Situs - Monica Monica (Humaniora, 2010)
Virtual world is now a mainstay many people promote themselves, goods, or their organizations. What is displayed in the virtual world associated with the role of a design is an interesting site and invites visitors to read and understand the message that the site owners want to convey. The design that attract not only in terms of its contents are complete but also in terms of appearance. This article describes a good selection of colors for a site, the application of typography for ease in reading the contents of site visitors, and a layout processing in accordance with the principles of design to design a site with well-ordered.